Optimization Design and Analysis of Sprocket Chain Plate Stage Driving Device - Houjin Zhou; Xue Wang; Yabin Wang; Yi Chen (Jixie chuandong)
The gear and rack drive devices are used to realize various movements of the stage in modern stage. Aiming at the problems of vibration and noise in the operation of rigid driving device， which affect the stability of stage motion and working environment， a sprocket chain plate driving structure is designed. The model of the driving device is established， and the driving system is simulated and dynamically analyzed， and the field test is carried out. The results show that the sprocket chain plate drive device has flexible effect， eliminates the defects of the rigid drive device， makes the stage transmission stable and reduces the noise. The driving device is applied in practical engineering， which proves the rationality of the design.